Nanozymes-based multifunctional platforms for uric acid detection in patients - Ojha R.P.; Srivastava S.K.; Srivastava M.; Prakash R. (My University, 2025)
Uric acid (UA), a metabolic by-product arising from purine metabolism, can result in hyperuricemia and related ailments like gout and kidney stones when accumulated excessively. In recent times, nanotechnology's emergence has opened avenues for innovative approaches in diagnostics and therapeutics. Notably, nanozymes, categorized as nanomaterials exhibiting inherent enzyme-like properties, have garnered significant interest for their potential applications in fabricating sensors for monitoring UA levels in patients. Nanozymes boast qualities, such as stability, tunability, cost-effectiveness, specificity, biocompatibility, and resilience, against challenging conditions. These attributes highlight their versatility, making them valuable for applications in sensors for the detection of ions, biomolecules, and disease biomarkers. This chapter comprehensively explores the conceptualization, fabrication, and multifaceted utilities of nanozyme-based platforms tailored for UA detection. © 2024 Elsevier Inc. All rights are reserved including those for text and data mining AI training and similar technologies.